STUDY ON RUTH PRAWERJHABVALA’S FICTION FEATURES CULTURAL CLASHES - Puja Kumari (International Journal of Multidisciplinary Research and Studies, 2021)
It was Ruth Prawer. Jhabvala Prawer was the daughter of Marcus and Eleonora Prawer and was born on May 7th, 1927 in the city of Cologne, Germany. Her family traced their roots to Germany, Poland, and Jewish Europe. She arrived in England in 1939, was naturalised as a British citizen in 1948, and graduated with a "Master of English" degree from Queen Mary College in London in 1951. Her year of arrival in England was 1939. She eventually settled down in India after marrying C. H. S. Jhabvala, an architect from that country. Jhabvala developed a genuine connection to the nation, although one that was fraught with tension. She has had the extraordinary experience of witnessing the subcontinent from the fortunate position of an insider but through the eyes of an outsider because to the fact that her husband is Indian and all three of her children, Renana, Ava, and Feroza, were born in India. Therefore, she draws inspiration for her scripts, books, and tales from the idea of being rooted in a culture and people because this is a topic that she is very familiar with.